Creation ”By Heat”. A Correspondence between Lithuanian and Indian Cosmogony (Lith. Tàpti – Skr. Tápati) - Razauskas, Dainius (Acta Orientalia Vilnensia, 2000)
Some semantic arguments for connecting Lith. tàpti ‘to become’ with Skr. tápati ‘warms, heats’, tapas– ‘(creative) heat’ (IE *tep– ‘to be warm’) are presented in the article. On the one hand, Lith. tàpti is used in the cosmogonic sense, on the other, cosmogony is unambiguously connected with warmth and heat in some Lithuanian sources (to begin with S. Daukantas). Skr. tapas–, as is well known, also means just cosmogonic heat in the Rig Veda (X.129.3). There are still some additional, secondary arguments. These consists of brooding connotations of Skr. tapas–. In its turn, the cosmogonic warmth in the mentioned and some other Lithuanian sources is expressed by the image of brooding too. The main concept underlying the “creation by heat” is that of hardening, consolidation, Lith. tvérti. And this Lithuanian verb has not only usuall cosmogonic notion but is used by village folk just in the sense of “hardening”, i.e. brooding of an egg as well. Etc.